Promising healing practices for interventions addressing intergenerational trauma among Aboriginal youth: A scoping review - Roy, Amrita; Noormohamed, Raheem; Henderson, Rita; Thurston, Wilfreda (First Peoples Child & Family Review, 2015)
There is growing recognition in Canada around the role of intergenerational trauma in shaping physical and mental health inequities among Aboriginal youth. We examined recommendations on best practices for addressing intergenerational trauma in interventions for Aboriginal youth. Academic-community partnerships were formed to guide this scoping literature review. Peer-reviewed academic literature and “grey” sources were searched. Of 3,135 citations uncovered from databases, 16 documents met inclusion criteria. The search gathered articles and reports published in English from 2001-2011, documenting interventions for Indigenous youth (ages 12-29 years) in Canada, the United States, New Zealand and Australia. The literature was sorted and mapped, and stakeholder input was sought through consultation with community organizations in the Calgary, Canada area. Recommendations in the literature include the need to: integrate Aboriginal worldviews into interventions; strengthen cultural identity as a healing tool and a tool against stigma; build autonomous and self-determining Aboriginal healing organizations; and, integrate interventions into mainstream health services, with education of mainstream professionals about intergenerational trauma and issues in Aboriginal health and well-being. We identified a paucity of reports on interventions and a need to improve evaluation techniques useful to all stakeholders (including organizations, funders, and program participants). Most interventions targeted individual-level factors (e.g., coping skills), rather than systemic factors (e.g., stressors in the social environment). By addressing upstream drivers of Aboriginal health, interventions that incorporate an understanding of intergenerational trauma are more likely to be effective in fostering resilience, in promoting healing, and in primary prevention. Minimal published research on evidence-based practices exists, though we noted some promising practices.